Total uterine artery blood volume flow rate in nulliparous women is associated with birth weight and gestational age at delivery. (January 2017) - McKelvey, A.; Pateman, K.; Balchin, I.; Peebles, D. M.; Rodeck, C. H.; David, A. L.
ABSTRACT: Objectives: To investigate the relationship between total uterine artery blood volume flow rate (TVFR) and birth weight and gestational age at delivery, and to establish normal ranges of TVFR throughout pregnancy. Methods: This was a prospective cohort study of 334 nulliparous women booking antenatal care at University College London Hospital between August 2008 and September 2009. Women underwent a transabdominal ultrasound examination of uterine arteries for measurement of TVFR at 12, 20 and 24 weeks' gestation. Pregnancy outcomes were recorded and linear regression was used to study the relationship between TVFR and gestational age at delivery and birth weight. Results: A total of 551 ultrasound scans were performed. There was a significant, positive correlation between TVFR at 11–13 weeks (TVFR1) and at 22–26 weeks (TVFR3) and birth weight. For every 100‐mL/min increase in TVFR1 and TVFR3, there was an increase in birth weight of 45 g and 27 g, respectively. There was also a positive association between TVFR1 and gestational age at delivery, with a 1.4‐day increase in gestational age for every 100‐mL/min increase of TVFR1. Conclusion: Ultrasound measurement of TVFR in the first trimester is significantly associated with both birth weight and gestational age at delivery. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.